Implementing Short Daily Conversation in Improving Students' Speaking Ability - Meiratnasari, Ayu; Syaikhoni, Yusuf; Ikhwan, Ali (Journal of Language, Literature and Teaching, 2024)
This research intended to describe how students' speaking ability improved through short daily conversations. The research belonged to classroom action research and consisted of two cycles. The setting of the research was in SMAN 1 Kretek, Bantul, Yogyakarta. The participants of this research were 25 students of XI IPA 2. The researcher gathered the data through conducting a pre-test, post-test 1, and post-test 2. In addition, to analyze the pre-test and post-test, the researcher used a descriptive quantitative approach describing the mean and the percentage of student improvement in each cycle. After implementing the research, the researcher found that short daily conversations can improve the student's speaking ability. It was shown from the result of the student's test scores. In each cycle, the student's score improved significantly. The pre-test result was low, with a mean score of 56.4. However, in the second result in the first cycle, the score was higher than the pre-test; the mean score was 66.12. Then, the last post-test in the second cycle was the highest; the mean score was 79.24. The conclusion was that teaching English using short daily conversations can improve students' speaking ability.Keywords: Speaking Skills, Short Daily Conversation, Speaking, Conversation, Action Research   .